Use of science to guide city planning policy and practice: how to achieve healthy and sustainable future cities. Issue 10062 (10th December 2016) - Sallis, James F; Bull, Fiona; Burdett, Ricky; Frank, Lawrence D; Griffiths, Peter; Giles-Corti, Billie; Stevenson, Mark
Summary: Land-use and transport policies contribute to worldwide epidemics of injuries and non-communicable diseases through traffic exposure, noise, air pollution, social isolation, low physical activity, and sedentary behaviours. Motorised transport is a major cause of the greenhouse gas emissions that are threatening human health. Urban and transport planning and urban design policies in many cities do not reflect the accumulating evidence that, if policies would take health effects into account, they could benefit a wide range of common health problems. Enhanced research translation to increase the influence of health research on urban and transport planning decisions could address many global health problems. This paper illustrates the potential for such change by presenting conceptual models and case studies of research translation applied to urban and transport planning and urban design. The primary recommendation of this paper is for cities to actively pursue compact and mixed-use urban designs that encourage a transport modal shift away from private motor vehicles towards walking, cycling, and public transport. This Series concludes by urging a systematic approach to city design to enhance health and sustainability through active transport and a move towards new urban mobility. Such an approach promises to be a powerful strategy for improvements in population health on a permanent basis.